Hardwood management and restoration of longleaf pine ecosystems may affect raccoon daytime resting sites. Issue 3 (11th October 2016) - Kirby, Ronald B.; Muller, Lisa I.; Chamberlain, Michael J.; Conner, Mike
Abstract: Fire‐maintained Pinus palustris (longleaf pine) ecosystems are species rich and considered a top conservation priority in the southeastern United States. Ground‐nesting species such as Gopherus polyphemus (gopher tortoise) and Colinus virginianus (northern bobwhite) thrive in longleaf ecosystems. However, the generalist carnivore Procyon lotor (raccoon) is a significant predator of these endemic ground nesters. In forested ecosystems, raccoons prefer hardwood‐dominated habitats. Removal of hardwood trees, which is a common longleaf pine ecosystem restoration tool, affects habitat use of this predator. We examined 269 daytime resting sites (DRS) associated with 31 radio‐collared adult raccoons (18 M, 13 F) during 2014–2015 on a longleaf pine‐dominated site in southwestern Georgia. We developed 26 a priori models using an information theoretic approach to evaluate factors affecting use of DRS by raccoons. The top two models (ΔAIC < 2) had combined model weights of 0.75 and contained tree diameter, tree type, presence of nearby hardwood, and distances to pine, hardwood, mixed forest, and agriculture as predictors. However, the only informative variables were tree type and tree diameter. Raccoons used DRS in all available forest types, but were less likely to use pine trees ( n = 7) relative to hardwoods ( n = 247), and there was a positive relationship with tree diameter. Females used smaller trees farther from agriculture and primary roads, and were closer to wetlands than those used by males. Hardwood removal from within longleaf pine ecosystem affects habitat use of this predator, specifically DRS.